Is future self‐relevance necessary to increase saving for retirement? A replication study. Issue 8 (29th May 2020) - Stockdale, Emma; Sanders, Michael
Abstract: Insufficient saving for retirement is one consequence of excessive discounting of the future but attempts to mitigate it often involve costly or time‐intensive personalized interventions. Marques, Mariano, Lima, and Abrams, by contrast, found that using a generic Future Time Perspective questionnaire to increase future "self‐relevance" was an effective method to increase money allocation to retirement when the salience of future aging was also higher. Originally conducted in Portugal, the present study aimed to replicate Marques et al's findings in the UK context. In the present study ( n  = 219), participants were shown a website advertising a financial product. The results support Marques and colleagues' assertion that, alone, a website priming future aging was insufficient to increase retirement savings in a money allocation task. However, in contrast to Marques et al's original findings, we find no evidence that future self‐relevance moderates the effect such that priming future aging becomes effective when individuals have higher future self‐relevance. Instead, we find that aging primes are ineffective at increasing retirement saving regardless of whether individuals are high or low in future self‐relevance. Possible explanations for this discrepancy in findings, including methodological and cultural differences, are explored as well as directions for future research.